Músicas populares en debates académicos, o ¿cada carancho a su rancho? - Prendes, Marcia Natividad (Universidad Nacional del Litoral, 2020)
In the present work some reflections related to the research that the author is developing in the framework of her graduate studies are presented. It is proposed to analyze ideas, concepts and methodological and critical perspectives contained in some texts and discussions on popular Argentine - Latin American music. These studies argue that it is difficult to insert and sustain popular music and musicology in academic settings, as well as to produce valid systematizations for their teaching. They insist that if their specificity is not considered, or they are not addressed under their own canons and characteristic production processes, pedagogical models designed for dominant musics continue to be reproduced, under a supposed «universality» approach, where everything becomes analyzable from the perspective of academic music. Those music that by omission are silenced, denied, not recognized, prohibited or censored, are excluded from the system and the academic fields, underestimating (in their reduction and simplification) the object of study and their own specificity.